Bridging Consumer Choices: The Role of Sustainable Packaging Logistics and Trust in E-Commerce Industry of Pakistan - Muhammad Bilal Ahmad; Fatima Shaukat; Fizza Rizvi; Muhammad Zulqarnain (Sustainable Business and Society in Emerging Economies, 2024)
Purpose: The study aims to investigate the impact of packaging, logistics, and ethical sources on consumer purchase behavior through Trust in the e-commerce industry of Pakistan. It